Reliability and Validity of the Chinese Nine-Item Basic Psychological Need Satisfaction Scale Based on Self-Determination Theory With Older Adults - Yang, Yuting; Yao, Miao; Yang, Yongwei; Ye, Qiong; Lin, Ting (Frontiers in Psychology, 2021)
Abstract Background: Self-Determination Theory distinguishes three basic human psychological needs: competence, relatedness, and autonomy. The measurement of these needs in populations of older adults has been limited and inadequate. Yet, results from such an assessment are likely to be valuable in policymaking, specifically toward the goal of healthy aging. Aim: The objective of this study was to test the reliability and validity of the Chinese version of the Basic Psychological Need Satisfaction Scale based on Self-Determination Theory with older adults. Methods: A total of 809 older adults were invited to participate in our study. We examined the Item Analysis, Internal Reliability, Factorial Validity, Criterion Validity, and Measurement Invariance across sex of a Chinese translation of the BPNS. Results: The findings demonstrated that the scale had a good factorial validity, criterion validity, and satisfactory internal reliability. All items were qualified according to Item Analysis (P<0.001). Cronbach's alpha for the total scale was 0.877. The coefficients of the three subscales were 0.826 (autonomy), 0.807 (competence), and 0.847 (relatedness). Exploratory Factor Analysis indicated 3 factors that explained 75.12% of the total variance. Confirmatory Factor Analysis showed measurement fit exceeded the recommended criteria in all cases. Measurement Invariance Analysis manifested that the factor loadings, factor variances and covariances, and residuals to measurement structure were invariant across male and female participants. Conclusions: The Chinese version of the Basic Psychological Need Satisfaction Scale based on Self-Determination Theory was proven to be reliable and valid. The usability of the scale to assess the satisfaction of the basic psychological needs of older adults in China was demonstrated.